Lactate dehydrogenase activity drives hair follicle stem cell activation - Flores, Aimee; Schell, John; Krall, Abigail S.; Jelinek, David; Miranda, Matilde; Grigorian, Melina; Braas, Daniel; White, Andrew C.; Zhou, Jessica L.; Graham, Nicholas A.; Graeber, Thomas; Seth, Pankaj; et al. (Nature cell biology, 2017)
Although normally dormant, hair follicle stem cells (HFSCs) quickly become activated to divide during a new hair cycle. The quiescence of HFSCs is known to be regulated by a number of intrinsic and extrinsic mechanisms. Here we provide several lines of evidence to demonstrate that HFSCs utilize glycolytic metabolism and produce significantly more lactate than other cells in the epidermis. Furthermore, lactate generation appears to be critical for the activation of HFSCs as deletion of lactate dehydrogenase (Ldha) prevented their activation. Conversely, genetically promoting lactate production in HFSCs through mitochondrial pyruvate carrier 1 (Mpc1) deletion accelerated their activation and the hair cycle. Finally, we identify small molecules that increase lactate production by stimulating Myc levels or inhibiting Mpc1 carrier activity and can topically induce the hair cycle. These data suggest that HFSCs maintain a metabolic state that allows them to remain dormant and yet quickly respond to appropriate proliferative stimuli. Flores et al. show that hair follicle stem cells rely on the production of lactate via the LDHA enzyme to become activated. Inducing Ldha through Mpc1 inhibition or Myc activation successfully reactivates the hair cycle in quiescent follicles.